Projetos de leitura literária em Caxias do Sul (2014 a 2022): contando e encantando - Aleknovic, Milena (My University, 2023)
The present work investigates the literary reading projects developed with children in Caxias do Sul city, in the 21 century, and their contribution in the formation of readers in the childhood. The realization of this survey takes place within the scope of the Graduate Program in Letters and Cultura (PPGLET) of the University of Caxias do Sul (UCS), with the line of research Literature and Cultural Processes. Carrying out such studies, this essay considers on interpretative bibliographical research, investigating the formation of the literary child reader from authors such as Abramovich (1997), Adler and Doren (2010), Bettelheim (2021), Franz (1990), Amnguel (1997), Ramos (2010), Zilberman (2001, 2003, 2005), among others. There is also a presentation of documents from the Quindim Institute collection, analyzing the literary reading projects and workshops carried out, such as Todxs against the coronavirus (2020), Summer workshops (2020) and Solidarity Christmas (2019). We also analyzed the books that from the Rede Recria project. [resumo fornecido pelo autor]
O presente trabalho investiga os projetos de leitura literária desenvolvidos com crianças na cidade de Caxias do Sul, no século XXI, e sua contribuição na formação de leitores na infância. A realização dessa pesquisa se dá no âmbito do Programa de Pós-Graduação em Letras e Cultura (PPGLET) da Universidade de Caxias do Sul (UCS), dentro da linha de pesquisa Literatura e Processos Culturais. Para realizar tal estudo, essa dissertação conta com pesquisa bibliográfica interpretativa, investigando a formação do leitor literário criança a partir de autores como Abramovich (1997), Adler e Doren (2010), Bettelheim (2021), Franz (1990), Manguel (1997), Ramos (2010), Zilberman (2001; 2003; 2005), entre outros. Também consta a apresentação de documentos do acervo do Instituto Quindim, analisando os projetos e oficinas de leitura literária realizados, como: Todxs contra o coronavírus (2020), Oficinas de verão (2020) e Natal solidário (2019). Também analisamos os livros que resultaram do projeto Rede Recria. [resumo fornecido pelo autor]
Keywords: Leitura - Projetos - Caxias do Sul (RS); Literatura infantojuvenil; Infância - Livros e leitura; Reading - Design - Caxias do Sul (Brazil); Children's literature; Infancy - Books and reading